Point-of-care diagnosis of COVID-19 disease based on antigen tests - Pohanka, Miroslav (Bratislavské lekárske listy, 2021)
AIMS: This review is focused on the laboratory diagnoses of the coronavirus disease 2019 (COVID-19) by recognizing the antigen of the causative agent SARS-CoV-2 virus. Various antigen tests are available in this moment and these tests are being further developed in order to reach a better diagnostic value. The issue is reviewed in a complex view. METHODS: In this work, a complex survey of the current literature was made. The relevant and recent papers related to antigen tests of COVID-19 are discussed and cited. Basic specifications of the antigen tests and competitive methods were also scrutinized in the current literature. RESULTS: The survey of the current literature (years 2019 ‒ 2021) was made and diagnostic methods like lateral flow tests (lateral flow immunochromatographic assay) and various types of biosensors were specified as tools for COVID-19 diagnosis and their application to be used as a point-of-care test is considered. CONCLUSIONS: Small hand-held assays applicable in the point-of-care conditions for diagnosis of COVID-19 by analysis of SARS-CoV-2 antigen are the means of a growing interest and these means undergo a significant development leading to the improvements of their specifications and applicability to the current praxis. Merit of the assays is discussed in this paper (Tab. 3, Fig. 2, Ref. 109).
Keywords: Humans; Immunoassay; ELISA; Enzyme-Linked Immunosorbent Assay; testování na COVID-19; COVID-19 Testing; imunoanalýza; SARS-CoV-2; COVID-19; Point-of-Care Testing; point of care testing; lidé